Operation and Maintenance Strategies for Hydropower : Handbook for Practitioners and Decision Makers - World Bank (World Bank, Washington, DC, 2020)
The Handbook for practitioners and decision makers seeks to raise awareness among utility managers, decision makers, and other stakeholders of the importance and benefits of developing robust operation and maintenance (O&M) strategies for existing and greenfield hydropower plants. This handbook also aims at providing guidance for owners in preparing and implementing a long-term O&M strategy, defined as an informed set of high-level information (including a diagnosis) and decisions towards effective and safe O&M of hydropower facilities, including (i) objectives to be reached, (ii) activities and organizational decisions to reach these objectives and (iii) adequate resources (human, financial…). Through eight steps, this handbook proposes a framework and processes to establish an O&M strategy adapted to local contexts. It also presents the basic principles of O&M for hydropower and provides examples of the consequences of inadequate O&M policies, programs, and procedures. The handbook was developed along and benefited from the lessons learned of six case-studies in Brazil, Pakistan, Nigeria, Liberia, Uganda, and Uruguay/Argentina and which are depicted in the companion report Operation and Maintenance Strategies for Hydropower: Six Case Studies. They gather examples and lessons learned from the implementation of O&M strategies, while sharing views on remaining challenges and future directions.